Forced Population Movements in the Ottoman Empire and the Early Turkish Republic: An Attempt at Reassessment through Demographic Engineering - Nesim Şeker (European Journal of Turkish Studies)
This article uses the concept of “demographic engineering” for the purpose of analyzing forced migration in the Ottoman Empire and early Turkish Republic. It defines demographic engineering in a wide sense, as ‘deliberate state intervention in population figures’ for political, ideological, strategic and economic reasons. It argues that reconsidering the issue of forced migration in the Ottoman Empire and the early Turkish Republic as a case of demographic engineering provides us with an analytical tool enabling comprehensive understanding of the state-directed population movements, and challenges the state-centered, nationalist outlook that has dominated the historiography on forced migration of the late Ottoman Empire.